Benefits of Neurohormonal Therapy in Patients With Continuous-Flow Left Ventricular Assist Devices. Issue 4 (April 2020) - Yousefzai, Rayan; Brambatti, Michela; Tran, Hao A.; Pedersen, Rachel; Braun, Oscar Ö.; Baykaner, Tina; Ghashghaei, Roxana; Sulemanjee, Nasir Z.; Cheema, Omar M.; Rappelt, Matthew; Baeza, Carmela; Alkhayyat, Abdulaziz; et al.
Abstract : Left ventricular assist devices (LVADs) have dramatically improved short-term outcomes among patients with advanced heart failure. While neurohormonal blockade (NHB) is the cornerstone of treatment for patients with heart failure with reduced ejection fraction, its effect after LVAD placement has not been established. We reviewed medical records of 307 patients who underwent primary LVAD implantation from January 2006 to September 2015 at two institutions in the United States. Patients were followed for at least 2 years post-LVAD implantation or until explantation, heart transplantation, or death. Cox regression analysis stratifying on center was used to assess associations with mortality. Neurohormonal blockade use was treated as a time-dependent predictor. Stepwise selection indicated treatment with angiotensin-converting enzyme inhibitors or angiotensin receptor blockers (ACEIs/ARBs) (hazard ratio [HR] = 0.53 [0.30–0.95], p = 0.03), age at the time of implantation (HR = 1.28 [1.05–1.56] per decade, p = 0.02), length of stay postimplantation (HR = 1.16 [1.11–1.21] per week, p < 0.01) and INTERMACS profile of 1 or 2 (HR = 1.86 [1.17–2.97], p < 0.01) were independent predictors of mortality. In this large, retrospective study, treatment with ACEIs or ARBs was an independent factor associated with decreased mortality post-LVAD placement. Abstract : Supplemental Digital Content is available in the text.